Implementasi Teknologi Terhadap Lingkungan Sekolah SMPN 85 Jakarta - Oktaviyanti, Ririn; Azka Aulia, Dinda; Sri Rahayu Pertiwi Dachi, Claudia; Fikalo Elistra, Nada; Kayowuan Lewoleba, Kayus; Subakdi, Subakdi (Journal of Comprehensive Science, 2024)
School environmental cleanliness is essential to create a healthy and productive learning environment. This study discusses various technologies that can be implemented in schools to improve effective and innovative cleanliness. These technologies include an app-based waste management system, the use of air quality sensors, and a digital platform to teach students about the importance of environmental cleanliness. Digital waste management systems enable schools to optimize waste collection and processing by monitoring and managing waste in real-time. Air quality sensors can also indicate levels of cleanliness and air pollution, which are essential for student health. In contrast, digital learning resources encourage students to actively participate in maintaining environmental cleanliness. Research shows that the use of technology not only improves school environmental cleanliness but also makes students more aware and responsible for cleanliness. In technology-based programs, students tend to have a positive attitude towards cleanliness and are more active in maintaining cleanliness. Consequently, incorporating technology into school environmental cleanliness has been shown to be effective in creating a cleaner, healthier, and more sustainable learning environment. For the future benefits of school environmental cleanliness, this study suggests further development of existing technologies.